KAIDAH HUKUM APLIKASI SERTA PERLINDUNGAN DAN TANGGUNGJAWAB DOKTER MELALUI APLIKASI - Gunawan Widjaja; Reza Sutrianingtyas Rahayu (JOURNAL OF LAW AND NATION, 2023)
Advances in technology allow everything to be done virtually remotely. This study aims to examine the use of applications by patients and doctors in providing services through applications and the responsibilities associated with providing services through these applications. This research is a juridical normative legal research. This study uses secondary data and qualitative analysis.